2013
DOI: 10.1155/2013/575080
|View full text |Cite
|
Sign up to set email alerts
|

Management of Uncomplicated Malaria in Underfives in Private and Public Health Facilities in South-Eastern Nigeria: A Clinical Audit of Current Practices

Abstract: Malaria remains a leading cause of underfive morbidity and mortality in sub-Saharan Africa. Effective case management is a strategy recommended by the World Health Organization for its control. A clinical audit of case management of uncomplicated malaria in underfives in health facilities in Cross River State, Nigeria, was conducted from January to March 2012. Data was extracted from patients' case records by trained medical personnel using pretested data extraction forms. Of the 463 case records reviewed, age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 10 publications
3
14
1
Order By: Relevance
“…In this study, the proportion of patients (99.4%) who received artemisinin-based compounds in their treatment was greater than that observed in a similar study by Dodoo et al [35]. Also, the high proportion (92.9%) of patient cards with prescribed ACTs observed in this study was greater than that found in similar studies done in Nigeria in 2008 [36], 2011 [37], and 2012 [38], which obtained proportions of 81.4%, 59.7%, and 88.3%, respectively. Findings from this aspect of this study suggest the adoption of the new antimalarial policy by prescribers at the hospital [39].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In this study, the proportion of patients (99.4%) who received artemisinin-based compounds in their treatment was greater than that observed in a similar study by Dodoo et al [35]. Also, the high proportion (92.9%) of patient cards with prescribed ACTs observed in this study was greater than that found in similar studies done in Nigeria in 2008 [36], 2011 [37], and 2012 [38], which obtained proportions of 81.4%, 59.7%, and 88.3%, respectively. Findings from this aspect of this study suggest the adoption of the new antimalarial policy by prescribers at the hospital [39].…”
Section: Discussioncontrasting
confidence: 65%
“…Patients who cannot tolerate oral treatment are to be given parenteral administration for one to two days until they can swallow, and initial parenteral treatment must always be followed by a full three-day course of ACT [45]. In a study at Nipid Health Center in Nigeria, 86.7% of 2010 and 92.1% of 2011 ACT prescription regimens representing 42.6% and 55.0% of all antimalarial prescriptions respectively, complied with WHO treatment regimen recommendations [36,38]. The percentage of encounters with correct antimalarial dosage (94.5%) obtained in this study was higher than those found in similar studies in Ghana (57.8%) [35] and Yemen (54.5%) [51].…”
Section: Discussionmentioning
confidence: 99%
“…15,20 In one drug utilization study in Nigeria in 2003, when ACT was introduced in the National Program, it was found that artemisinin derivatives were prescribed to 15.8% of falciparum cases, only 3% of whom received ACT (artemether-lumefantrine being the commonest agent); another study in Nigeria in 2012 reported increase and appropriate use of ACT to over 60% of children with falciparum malaria. 12,13 In this study, quinine (11.11% in children and 8.33% in adults) and artesunate (22.22% in children and 14.58%% in adults) in injection formula were used in falciparum malaria patients who were suffering from severe malaria and were admitted in the hospital. In one study from a tertiary care hospital in Eastern India showed that artesunate (48.1%) and mefloquine (25.9%) were the most common antimalarials for falciparum malaria.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-malarial prescribing pattern in Nigeria showed that most of the patients were treated without parasitological confirmation, which now is discouraged in guidelines, also poor adherence to National and WHO guidelines is a common practice in Nigeria. 12,13 In rural Kenya, lack of adherence to malaria treatment guideline was associated with irrational prescribing. 14 Data on anti-malarial use pattern in India are scanty.…”
mentioning
confidence: 99%
“…16 A 2012 Nigerian audit of the management of children with malaria under 5 years old found that only 28.5% of patients had any diagnostic test performed. 17 Of these, just 18.9% had a RDT, showing underuse of what could be an important resource in combating malaria in developing countries.…”
Section: Resultsmentioning
confidence: 99%